Adverse Selection as a Policy Instrument - Cicala, Steve,Hémous, David,Olsen, Morten (National Bureau of Economic Research, 2022)
This paper applies principles of adverse selection to overcome obstacles that prevent the implementation of Pigouvian policies to internalize externalities. Focusing on negative externalities from production (such as pollution), we consider settings in which aggregate emissions are known, but individual contributions are unobserved by the government. We evaluate a policy that gives firms the option to pay a tax on their voluntarily and verifiably disclosed emissions, or pay an output tax based on the average rate of emissions among the undisclosed firms. The certification of relatively clean firms raises the output-based tax, setting off a process of unraveling in favor of disclosure. We derive sufficient statistics formulas to calculate the welfare of such a program relative to mandatory output or emissions taxes. We find that the voluntary certification mechanism would deliver significant gains over output-based taxation in two empirical applications: methane emissions from oil and gas fields, and carbon emissions from imported steel
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Umweltbelastung; Umweltabgabe; Ökosteuer; Pigou-Steuer; Umweltpolitik; Adverse Selektion; Internalisierung externer Effekte; Wohlfahrtsanalyse; Asymmetric and Private Information; Mechanism Design; Taxation; Subsidies; and Revenue; International Fiscal Issues; International Public Goods; Energy; Environmental; Health; and Safety Law; Economics of Regulation; Climate; Natural Disasters and Their Management; Global Warming